Analisis Faktor Dekadensi Moral Generasi Z dan Solusinya dalam Konseling Islam - Wijayanti, Syaputri; Abdurrahman, Zulkarnain (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The rapid development of science and technology, while offering positive impacts, also presents significant challenges, notably the moral decadence among the youth, including Generation Z. This research aimed to identify the specific forms and predominant factors contributing to the moral decadence of Generation Z in the Tanjung Pura District, specifically Desa Pematang Cengal, and to formulate comprehensive solutions through an Islamic counseling approach. This qualitative study employed a descriptive approach, involving 20 purposively selected participants: 15 Generation Z youth (aged 15-25) and 5 community leaders from Desa Pematang Cengal, Tanjung Pura. Data were collected through in-depth interviews, observation, and documentation. Data analysis utilized the Miles and Huberman model (data reduction, data display, conclusion drawing/verification) with a thematic analysis approach, and data validity was ensured through source and method triangulation. Key findings reveal that prevalent forms of moral decadence include criminality, Westernized lifestyle changes, bullying, substance abuse (NAPZA and alcohol), online gambling, and free association leading to premarital sex, alongside a decline in religious practices and respect. The primary contributing factors identified were weak religious understanding and practice, suboptimal family environment and parental roles, negative peer influence, a permissive community environment, and the unfiltere impact of technology. The study proposes that solutions lie in a holistic and adaptive Islamic counseling approach, emphasizing spiritual strengthening, enhancing the roles of family, school, and community, and leveraging technology positively. This research underscores the urgent need for an integrated and contextualized Islamic counseling framework to fortify the moral resilience of Generation Z in the digital era, particularly within rural communities.